2013
DOI: 10.1016/j.jmb.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Disease-Causing Missense Mutations

Abstract: Genetic variations resulting in a change of amino acid sequence can have a dramatic effect on stability, hydrogen bond network, conformational dynamics, activity and many other physiologically important properties of proteins. The substitutions of only one residue in a protein sequence, so-called missense mutations, can be related to many pathological conditions, and may influence susceptibility to disease and drug treatment. The plausible effects of missense mutations range from affecting the macromolecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
241
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(246 citation statements)
references
References 191 publications
(209 reference statements)
4
241
0
1
Order By: Relevance
“…(28)(29)(30)(31) We utilized the free energy perturbation (FEP) (32,33) method based on standard molecular dynamics sampling 6 and also several other methods that are known to be fast to obtain a consensus prediction. Below, the FEP method implementation in the current work is described along with other methods and webservers utilized.…”
Section: In Silico Modelingmentioning
confidence: 99%
“…(28)(29)(30)(31) We utilized the free energy perturbation (FEP) (32,33) method based on standard molecular dynamics sampling 6 and also several other methods that are known to be fast to obtain a consensus prediction. Below, the FEP method implementation in the current work is described along with other methods and webservers utilized.…”
Section: In Silico Modelingmentioning
confidence: 99%
“…Many disease-causing nsSNPs may affect structure and stability of proteins, thereby altering or preventing their function (Dabhi & Mistry, 2014;Doss & NagaSundaram, 2012;Guo, Ning, Ren, Liu, & Yao, 2012). The magnitude of mutation's effect on protein stability can be quantified by changes in the folding free energy (ΔΔG) (Stefl et al, 2013). In this study, analysis of P5CR stability by the I-Mutant program reveals that the identified mutants have lower structural stability than the WT form.…”
Section: Discussionmentioning
confidence: 94%
“…It is well established that protein function is closely related to its stability (Stefl, Nishi, Petukh, Panchenko, & Alexov, 2013). Many disease-causing nsSNPs may affect structure and stability of proteins, thereby altering or preventing their function (Dabhi & Mistry, 2014;Doss & NagaSundaram, 2012;Guo, Ning, Ren, Liu, & Yao, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[21]. It is to be expected that the significance for life science will increase because of their mutual influence on the conformational changes that may result in loss of specificity [22].…”
Section: The Pressure (Gpa) As a Function Of The Lattice Parameter(a)mentioning
confidence: 99%